Clinical Consequences of Immune Response to CT Upper Genital Tract Infection in Women - J. Henry-Suchet; M. Askienazy-Elbhar; J. Orfila (Hindawi Limited, 1996)
C. TRACHOMATIS (CT) infections of the upper genital tract in women are either acute, sub acute or chronic. CT infection has a tendency to be chronic, latent and persistent as a consequence of the host immune reaction to CT major outer membrane protein, 57 Kd heat shock protein and lipopolysaccharide. Chlamydial persistence can be induced as a result of inflammatory and/or immune regulated cytokines, Interferon γ depletion of tryptophan causes a stress response involving development of abnormal forms with increased levels of stress response proteins which maintain host immune responses with continuous fibrin exudate.